Low‐Dose Irinotecan Improves Advanced Lupus Nephritis in Mice Potentially by Changing DNA Relaxation and Anti–Double‐Stranded DNA Binding. Issue 8 (August 2014) - Frese‐Schaper, Manuela; Keil, Andreas; Steiner, Selina K.; Gugger, Mathias; Körner, Meike; Kocher, Gregor J.; Schiffer, Lena; Anders, Hans‐Joachim; Huynh‐Do, Uyen; Schmid, Ralph A.; Frese, Steffen
<x xml:space="preserve">Abstract</x> Objective Despite clear advances in the treatment of systemic lupus erythematosus (SLE), many patients still present with refractory lupus nephritis, requiring new treatment strategies for this disease. This study was undertaken to determine whether reduced doses of the topoisomerase I (topo I) inhibitor irinotecan, which is known as a chemotherapeutic agent, suppress SLE in (NZB × NZW)F1 (NZB/NZW) mice, and to evaluate the potential mechanism by which irinotecan influences the course of SLE. Methods NZB/NZW mice were treated with low‐dose irinotecan beginning at either 24 weeks of age or established glomerulonephritis, defined as proteinuria of grade ≥3+. Binding of anti–double‐stranded DNA (anti‐dsDNA) antibodies was measured by enzyme‐linked immunosorbent assay (ELISA), and DNA relaxation was visualized by gel electrophoresis. Results Significantly reduced irinotecan doses improved lupus nephritis and prolonged survival in NZB/NZW mice. The lowest dose successfully used for the treatment of established murine lupus nephritis was >50 times lower than the dose usually used for chemotherapy in humans. As a mechanism, low‐dose irinotecan reduced B cell activity. However, the levels of B cell activity in irinotecan‐treated mice were similar to those in BALB/c mice of the same age, suggesting that irinotecan did not induce clear immunosuppression. In addition, incubation of dsDNA with topo I increased binding of murine and human anti‐dsDNA antibodies, showing for the first time that relaxed DNA is more susceptible to anti‐dsDNA antibody binding. This effect was reversed by addition of the topo I inhibitor camptothecin. Conclusion Our findings indicate that topo I inhibition may be a novel and targeted therapy for SLE.